2013
DOI: 10.1590/s1413-294x2013000300002
|View full text |Cite
|
Sign up to set email alerts
|

Gestantes portadoras de HIV/AIDS: aspectos psicológicos sobre a prevenção da transmissão vertical

Abstract: ResumoA gestação, em geral, repercute emocionalmente na mulher e, mais intensamente, quando associada a uma situação clínica comprometedora da saúde do filho, como na possibilidade de transmissão vertical do HIV. Nesse contexto, o presente estudo teve por objetivo investigar as significações subjetivas das gestantes portadoras de HIV sobre a realização das ações de prevenção da transmissão vertical. Para tanto, recorreu-se a uma investigação do tipo transversal, de natureza descritiva e exploratória, com abord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
21

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 22 publications
0
18
0
21
Order By: Relevance
“…At this meeting, the member States of the UN report, in a statement, the commitment for 2020 to reduce new infections of HIV and the mortality rates of AIDS to less than 500 thousand a year. Some preventative measures are: realization of elective cesarean section, zidovudine monotherapy (AZT), antiretroviral management, administration of AZT during delivery and use of oral antiretroviral by the newborn exposed during birth until the 42nd day of life, and replacement of natural breastfeeding by bottle-feeding (47)(48)(49) .…”
Section: Discussionmentioning
confidence: 99%
“…At this meeting, the member States of the UN report, in a statement, the commitment for 2020 to reduce new infections of HIV and the mortality rates of AIDS to less than 500 thousand a year. Some preventative measures are: realization of elective cesarean section, zidovudine monotherapy (AZT), antiretroviral management, administration of AZT during delivery and use of oral antiretroviral by the newborn exposed during birth until the 42nd day of life, and replacement of natural breastfeeding by bottle-feeding (47)(48)(49) .…”
Section: Discussionmentioning
confidence: 99%
“…They externalized fear of vertical HIV transmission during pregnancy, the side effects of medication, prejudice about the disease, and at the same time voiced feelings of overcoming through self-care, confidence in adhering to their therapy, and attempting to overcome prejudice and the diagnosis of HIV recently discovered prenatally, even if absorbing this is not an easy task. 1,[6][7][8][9][10] Studies have shown that although HIV-positive pregnant women have reported experiencing a normal pregnancy, peculiar situations are evidenced in the daily life of pregnant women who acquired this infection.…”
Section: Discussionmentioning
confidence: 99%
“…Feelings such as hope that all progresses well in the pregnancy, being able to have a child, being capable of taking the medication, witnessing the healing of AIDS, having a long life, having a "normal" life, and raising a healthy child are also commonly found in other studies. 8,9,12 Faced with the possibility of vertical transmission, most pregnant women living with HIV are engaged, adhering to their treatment and attending their appointments; learning about the disease, its evolution, and the manifestation of signs and symptoms; and changing their lifestyle in order to encourage the promotion of health. 1 The child therefore becomes the strength and encouragement to overcome the obstacles of living with HIV, thus benefiting the physical and mental health of the pregnant women.…”
Section: 11mentioning
confidence: 99%
See 2 more Smart Citations